Trends and Implementation of Virtual Laboratories in Fostering Thinking Skills in Higher Education: An Integrative Review - Gunawan Gunawan; Baiq Nabila Saufika Zainuri; Fahmi Yahya (Indonesian Journal of Applied Science and Technology, 2022)
Digital transformation in higher education has triggered the repositioning of virtual laboratories as strategic instruments to support 21st-century competencies. This integrative review aims to map the developmental trends of virtual laboratory technology and its implementation patterns in stimulating university students' higher-order thinking skills (critical thinking, creative thinking, and problem-solving). Through a critical synthesis of the empirical literature, a distinct media migration trend was identified, evolving from linear interactive two-dimensional (2D) desktop simulations at the beginning of the decade toward immersive three-dimensional (3D) technologies, Virtual Reality (VR), Augmented Reality (AR), and cloud computing ecosystems by the end of the decade. Empirical evidence indicates that the implementation of virtual laboratories effectively stimulates thinking skills by providing a risk-free learning environment and real-time parameter manipulation features. However, this review highlights critical academic debates regarding extraneous cognitive overload and the potential distortion of scientific reality caused by overly idealized simulation data. Optimal effectiveness is achieved when virtual laboratories are integrated via a blended learning model to serve as a pre-practicum bridge. This review offers substantial implications for lecturers and instructional designers in aligning simulation technology with active learning syntaxes in higher education.